Blood pressure lowering for prevention of episodic migraine: results of a pilot randomized, placebo-controlled trial of combination blood pressure lowering medication with propranolol - Carcel, Cheryl; Haghdoost, Faraidoon; Davies, Leo; Cordato, Dennis; Griffiths, Lyn; Balicki, Grace; Li, Qiang; Freed, Ruth; Anderson, Craig S.; Zagami, Alessandro S.; Delcourt, Candice; Rodgers, Anthony (Frontiers in Neurology, 2025)
BackgroundBeta blockers are effective in migraine prevention. Low-dose combination therapy of blood pressure lowering is likely to lower blood pressure more than a beta-blocker, but there are no data on comparative efficacy of these treatments in migraine prophylaxis.MethodsA double-blind, randomized, pilot trial in participants with episodic migraine to assess feasibility and tolerability of low-dose triple combination BP lowering (telmisartan 20 mg, amlodipine 2.5 mg and indapamide 1.25 mg) vs. propranolol 160 mg daily vs. matching placebos. The primary outcome was monthly headache days.ResultsBetween March 2017 and June 2018, 378 participants were screened and 30 were randomized (8%). The key reasons for ineligibility among screen failures were low blood pressure (86, 26%), unwilling to participate in a drug trial (76, 23%) and not meeting episodic migraine criteria (54, 16%). Among those randomized, mean age was 49 years, 83% female, baseline migraine frequency was 67 h, aura present in 47%, mean baseline BP was 131/87 mmHg. As expected from a small pilot, the confidence intervals for treatment effect estimates were wide: reduction in monthly headache days for the low-dose triple were −0.6 (95% confidence interval [CI] −2.9, 1.8) and for propranolol −1.1 (95% CI −3.8, 1.6) compared to placebo. Tolerability was good, there were no dropouts from adverse events.ConclusionAs a pilot study, the trial was not powered to detect efficacy; larger trials are required to determine the effect of low-dose triple combination blood pressure lowering on migraine. The medication was safe and well tolerated by participants with migraine; it is likely that study co-design with people with lived experience of migraine will benefit recruitment into the trial.Clinical trial registrationACTRN12616000937415, https://anzctr.org.au/.